Closing the gap: increases in life expectancy among treated HIV-positive individuals in the United States and Canada. - Hasina Samji; Angela Cescon; Robert S Hogg; Sharada P Modur; Keri N Althoff; Kate Buchacz; Ann N Burchell; Mardge Cohen; Kelly A Gebo; M John Gill; Amy Justice; Gregory Kirk; et al. (PLoS ONE, 2013)
Background Combination antiretroviral therapy (ART) has significantly increased survival among HIV-positive adults in the United States (U.S.) and Canada, but gains in life expectancy for this region have not been well characterized. We aim to estimate temporal changes in life expectancy among HIV-positive adults on ART from 2000-2007 in the U.S. and Canada. Methods Participants were from the North American AIDS Cohort Collaboration on Research and Design (NA-ACCORD), aged ≥20 years and on ART. Mortality rates were calculated using participants' person-time from January 1, 2000 or ART initiation until death, loss to follow-up, or administrative censoring December 31, 2007. Life expectancy at age 20, defined as the average number of additional years that a person of a specific age will live, provided the current age-specific mortality rates remain constant, was estimated using abridged life tables. Results The crude mortality rate was 19.8/1,000 person-years, among 22,937 individuals contributing 82,022 person-years and 1,622 deaths. Life expectancy increased from 36.1 [standard error (SE) 0.5] to 51.4 [SE 0.5] years from 2000-2002 to 2006-2007. Men and women had comparable life expectancies in all periods except the last (2006-2007). Life expectancy was lower for individuals with a history of injection drug use, non-whites, and in patients with baseline CD4 counts <350 cells/mm(3). Conclusions A 20-year-old HIV-positive adult on ART in the U.S. or Canada is expected to live into their early 70 s, a life expectancy approaching that of the general population. Differences by sex, race, HIV transmission risk group, and CD4 count remain.